Bạn ơi A hình như là = 2009.2011
Có : A = 2009.2011=2009.(2010+1)=2009.2010+2009=(2009.2010+2010)-1=2010.(2009+1)-1=2010^2-1
Vì 2010^2-1 < 2010^2
=> A < B
k mk nha
Ta có:
\(A=2009.2001\)
\(B=2010^2\)
\(B=2010.2010\)
Vì 2010 > 2009, 2010 > 2001
\(\Rightarrow2009.2001< 2010.2010\)
\(\Rightarrow A< B\)
Nếu đề bài A bằng 2009.2011 thì làm như sau:
Áp dụng HĐT (a-b)(a+b) bằng a2 - b2 , ta có:
\(A=2009.2011\)
\(A=\left(2010-1\right)\left(2010+1\right)\)
\(A=2010^2-1^2\)
\(A=2010^2-1\)
Mà 20102 - 1 < 20102
\(\Rightarrow A< B\)